Prognostic signficance of wheeze for poor health outcomes in children aged 4 to 9 years - Cooper, S; Marks, G; Ampon, R; Poulos, L; Belousova, E; Reddel, H (My University, 2012)
Background: Not all children who wheeze have asthma. However, many epidemiological studies of asthma in children rely on parental report of wheezing. Aim: To establish if parental report of wheezing has prognostic significance. Methods: We used data from kindergarten (waves 1, 2 & 3) and infant (waves 2&3) cohorts of the Longitudinal Study of Australian Children linked to Medical and Pharmaceutical Benefits Scheme databases. Children from the infant cohort were age 4-5 years at wave 2 and children from the kindergarten cohort were 4-5 and 6-7 years at waves 1&2. Excess health care utilisation was defined as any hospitalisation or ED visit in the last year and/or ≥13 GP visits during the last 2 years. We estimated relative risk (RR) of poor health outcomes if wheezing was reported two years earlier, adjusted for asthma diagnosis status at that time, using a generalised linear model adjusted for survey design. Results: Outcome at two-year follow-up Wheeze Asthma Dx (n = 8717 children) RR 95% CI RR 95% CI Excess health care utilisation 1.4 1.4 -1.5 1.2 1.1-1.3 Poor or fair health status 1.7 1.2-2.2 1.8 1.3-2.5 Poor sleeping patterns or habits 1.5 1.3-1.8 1.2 1.0-1.5 School absence ≥ 4 days in last 4 weeks 1.5 1.2-1.8 1.1 0.9-1.3 Problems participating in sports/exercise 0.97 0.8-1.2 1.4 1.2-1.6 Choosing inactive or sedentary pastimes 0.99 0.9-1.1 1.1 1.0-1.2 Wheezing was associated with an increased risk for subsequent excess health care utilisation, poor/fair health status, poor sleep patterns and school absences, independent of the asthma diagnosis status. It was not associated with problems participating in sports or in choosing inactive/sedentary pastimes. Conclusion: These findings support the predictive validity of wheezing as a marker of disease in young children. Support: Australian Institute of Health and Welfare & Australian Government Department of Health & Ageing.
Keywords: Health -- Medications; Children; Health and wellbeing; Health; Children; Medications; Health and wellbeing